Alternative lenses for viewing how China has built its accounting and auditing profession. Issue 1 (4th November 2020) - Macve, Richard H.
Abstract : Purpose: The paper reviews some theoretical approaches that have been adopted for understanding the drivers and achievements of the Chinese professional project and the challenges it faces for the future, as a complement and a contrast to previous histories of China and to studies of other developing economies. Design/methodology/approach: Based mainly on evaluating the information as obtained from the interviews in mainland China, in Hong Kong and in London reported by Macve (2020), complemented by other published histories. Findings: China remains a paradox. Since the "reform and open" policy began in 1978 it has been transformed from one of the poorest countries to one of the economically most powerful in just some 40 years. However it remains (per capita) a "developing country"/"emerging economy" and ideologically a Communist country. While the accounting profession in the USA and UK has developed "from the bottom up" over more than a century and a half, the Chinese profession has effectively been created "from the top down" in under 25 years. The paper outlines alternative theorizations of the major stages in this achievement, in the context of the continuing rapid growth of China's economy and its stock markets, and of the overseas expansion of its manufacturing and increasingly service-oriented base. Research limitations/implications: Space has restricted the analysis here to a general overview. Application of Gramsci's hegemony theory is argued to be inappropriate in the context of understanding China's professional project. Instead, this study is framed within the neo-institutional theory of "linked ecologies" originally developed to examine "Western" developments and extended to the emergence of glocalization, while offering a comparison with related theorization of Russia's post-Communist development. Further theoretical development outside the Western neo-liberal context is called for. Originality/value: The paper demonstrates how accounting and auditing's development in this globally significant context has differed from that in other developing and transitional economies, reflecting in particular the proactive agency of the state. Given China's economic power, fuller understanding of the interrelated factors shaping its development is important for understanding the likely future shaping of the worldwide profession.